Organic - Inorganic Hybrid Luminescent Composite for Solid-state Lighting - Chung, Do Ngoc; Tuan, Le Trac; Hao, Tran Cong; Hieu, Do Ngoc; Dinh, Nguyen Nang; Duong, Pham Hong (Communications in Physics, 2013)
White light emitting diodes (WLEDs) made by coating organic and inorganic hybrid composites on blue LED chips. Y3Al5O12:Ce (YAG:Ce) nano inorganic powder prepared by low-temperature Sol-Gel method exhibited broad green emission with the peak at 521 nm. Poly[2-methoxy-5-(2’-ethyl-hexyloxy)-1,4-phenylene vinylene] (MEH-PPV) polymer has high luminescence efficiency and red emission peak at 590 nm. The white light was obtained by mixing blue light from emission of the blue LED chip - Indium Gallium Nitride (InGaN) and green-red light from the fluorescence of nano- YAG:Ce and MEH-PPV polymer hybrid composite. The hybrid nanocomposite-based WLEDs exhibited broad band emission spectra from blue light to red wavelengths and provided the white light with a CIE-1931 coordinate of x = 0.2986, y = 0.2620 and a colour rendering index Ra = 84.36. The results suggest a potential application of nanocomposite based WLEDs in efficient solid-state lighting.